2007
DOI: 10.1007/s10717-007-0015-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase composition and morphology of products of combustion of ferrosilicon in nitrogen

Abstract: The results of a study of silicon nitride phase formation in combustion of ferrosilicon in gaseous nitrogen are reported. It was shown that formation of a-or b-modifications of silicon nitride is basically determined by the composition of the batch for self-propagating high-temperature synthesis. When ammonium chloride was added to the initial ferrosilicon, a combustion product with a high (up to 80%) a-Si 3 N 4 content is formed, while dilution with the final product and magnesium fluoride results in predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…%) and a small amount of un-nitrided Fe 3 Si (~15 wt. %) [16,17]. With the main phase being Si 3 N 4 , Fe-Si 3 N 4 inherits the excellent comprehensive properties of pure Si 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%
“…%) and a small amount of un-nitrided Fe 3 Si (~15 wt. %) [16,17]. With the main phase being Si 3 N 4 , Fe-Si 3 N 4 inherits the excellent comprehensive properties of pure Si 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Si 3 N 4 -SiC materials with uniformly dispersed metallic plastic phase is expected to have higher thermal conductivity and thermal shock resistance in favour of enhancing blast furnace cooling rate. At present, the research on Fe 3 Si-Si 3 N 4 -SiC materials is rarely reported in domestic and oversea research [11][12][13][14], this research hopes to provide some useful reference.…”
Section: Introductionmentioning
confidence: 99%
“…The basic mechanisms of this process are described in [3,4]. For the interaction of ferrosilicon with nitrogen in a combustion regime heat is released as a result of the interaction of silicon with nitrogen:…”
mentioning
confidence: 99%